2010
DOI: 10.2169/internalmedicine.49.2913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of the Responsible Lesion for Dysarthria in the Cerebellum

Abstract: There have been few reports describing the lesion for cerebellar dysarthria. We compared MRI findings of 4 reported patients (including our previously reported patient) to that of our patient who showed ataxic speech and ataxic gait. The lesions of 4 patients involved lobulus quadrangularis and lobulus simplex, and the lesion of the present patient involved lobulus semilunaris superior and lobulus simplex. Since lobulus simplex and lobulus quadrangularis were involved in many patients, we speculated that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Similarly, using fMRI, Urban (2013) described cerebellar activation during speech production. Ogawa, Yoshihashi, Suzuki, Kamei, and Mizutani (2010) proposed that cerebellar dysarthria is characterized by ‘… ataxic speech, and is mainly caused by impairment of the upper cerebellar hemisphere in the distribution of the superior cerebellar artery (SCA)’ (p. 861). The link between the known cerebellar differences in persons with DS paired with the motor speech disorder results and ataxic dysarthria findings further support the role of the cerebellum in speech production and the potential causative role of cerebellar dysfunction in motor speech disorder and intelligibility deficits in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using fMRI, Urban (2013) described cerebellar activation during speech production. Ogawa, Yoshihashi, Suzuki, Kamei, and Mizutani (2010) proposed that cerebellar dysarthria is characterized by ‘… ataxic speech, and is mainly caused by impairment of the upper cerebellar hemisphere in the distribution of the superior cerebellar artery (SCA)’ (p. 861). The link between the known cerebellar differences in persons with DS paired with the motor speech disorder results and ataxic dysarthria findings further support the role of the cerebellum in speech production and the potential causative role of cerebellar dysfunction in motor speech disorder and intelligibility deficits in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Dysarthria results in slurred and irregular speech with impaired pronunciation, due to a lack of coordination of the motor-speech system [42]. It results from a combination of ataxia and dystonia and involves pathologies in the cerebellum and basal ganglia.…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI (fMRI) studies in healthy volunteers show that the cerebellar representation of the tongue and orofacial muscles corresponds to that of the area involved in patients with cerebellar dysarthria due to focal vascular lesions (Urban et al 2003). Impairment of the upper cerebellar hemisphere in the territory of the superior cerebellar artery results in dysarthria (Ogawa et al 2010). Combined parametric data (measurements at the acoustic speech signal, tracking of articulatory movements and fMRI studies) have contributed to redefine the concept of ataxic dysarthria and indicated the cerebellum to support several aspects of speech processing.…”
Section: Dysarthria and Other Speech Deficitsmentioning
confidence: 99%